2008
DOI: 10.1159/000155613
|View full text |Cite
|
Sign up to set email alerts
|

Collagen/Endogenous Thrombin-Induced Platelet Aggregation in Cord versus Adult Whole Blood

Abstract: Background: In previous studies, neonatal platelets have been shown to be hypoaggregable to various agonists when compared with adult platelets. Objectives: It was the aim of this study to investigate the aggregability of neonatal versus adult platelets when the physiological relevant agonist collagen/endogenous thrombin is used. Methods and Results: Whole blood (WB) aggregation experiments employing the impedance method revealed the same responsiveness of neonatal and adult platelets to collagen/endogenous th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Platelet counts were approximately the same, hematocrit and white blood cell count were higher in cord versus adult WB, as shown previously [22] .…”
Section: Cell Counts Pro-and Anticoagulant Factors In Neonates Versusupporting
confidence: 87%
“…Platelet counts were approximately the same, hematocrit and white blood cell count were higher in cord versus adult WB, as shown previously [22] .…”
Section: Cell Counts Pro-and Anticoagulant Factors In Neonates Versusupporting
confidence: 87%
“…Finally, there could be other patterns of platelet receptors as well as platelet binding proteins supporting hemostasis differently on newborn platelets than on adult platelets. Additionally different signal transduction pathways in newborn platelets may compensate for the observed impaired ones, such as reduced GTPase activity of G q coupled receptors and lower serotonin excretion upon collagen/endogenous thrombin stimulation (15,16).…”
Section: Vergleichende Bestimmung Des Gehalts Von Par1 Gpib-ix-v Anmentioning
confidence: 99%
“…tor plus collagen [7] . In contrast to these in vitro studies, bleeding times in healthy term neonates have been shown to be shorter than in adults [8][9][10][11][12] .…”
mentioning
confidence: 99%